Carbon-mineralized artificial stone based on solid waste and preparation process of carbon-mineralized artificial stone

By using solid waste raw materials, aggregate and other combination raw materials in solid waste mineralization technology, and using pre-mineralization and graded mineralization technology, combined with the preparation method of admixtures, the mineralization reaction conditions are optimized, and the problems of insufficient penetration of CO2 and long mineralization cycle are solved, and the high mechanical strength, high carbon sequestration rate and uniformity of carbon mineralized artificial stones are improved.

CN119591372APending Publication Date: 2025-03-11SUZHOU TONGCUI CARBON NEUTRALITY TECH CO LTD

Patent Information

Application Number
CN202411724235.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, CO2 is insufficient penetration of solid waste body, resulting in limited mineralization depth and carbon mineralized artificial stone performance stability, long mineralization period and low carbon fixation uniformity.

Method used

Solid waste raw materials, aggregates, defoaming agents, water reducing agents, retarders and admixtures are used as raw materials. Through pre-mineralization and graded mineralization technology, combined with the preparation method of admixtures, the mineralization reaction conditions are optimized, including adjusting CO2 concentration, mineralization pressure and temperature to achieve internal and external uniformity and admixture reaction.

Benefits of technology

The mineralization cycle is significantly shortened, the mechanical strength, carbon fixation rate and the uniformity of the inner and outer layers of carbon mineralized artificial stones have been improved, and the problems of insufficient mineralization and low carbon fixation uniformity in the prior art have been solved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

According to the carbon mineralization artificial stone based on the solid waste, the solid waste raw material, the aggregate, the defoaming agent, the water reducing agent, the retarder and the additive serve as raw materials, and the prepared carbon mineralization artificial stone is high in carbonization degree and excellent in mechanical strength. The additive prepared by taking an aminoguanidine compound, a silane coupling agent and a diacid compound as raw materials is introduced, so that a substance for filling pores and CO2 gas can be generated in a system, a pore structure is optimized, internal mineralization is realized, and the binding force among the components in the system can be enhanced; therefore, the carbonization degree, the carbon sequestration rate and the mechanical strength of a carbon mineralization product are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solid waste recovery and CO2 capture technology, B09B3 / 00, and in particular to a solid waste-based carbon mineralized artificial stone and a preparation process thereof. Background Art

[0002] Mineralization technology provides an effective resource recycling method for a large amount of alkaline solid waste in my country. It can not only absorb a large amount of alkaline solid waste and solve the problem of pollution and land occupation, but also effectively seal the CO2 waste gas emitted in industrial activities, which has the effect of reducing pollution and carbon emissions. However, the technical defect of insufficient penetration of CO2 into solid waste blanks is still a factor restricting the mineralization depth and the stability of the performance of carbon mineralized artificial stone. At present, the main methods to solve the mineralization depth and mineralization uniformity are: 1. Adding cementitious materials or sintering materials to solid waste to reduce the early surface mineralization degree of the blank, and using the water hardness of cementitious materials to promote the strength of the product; 2. Increasing the purity of flue gas and extending the mineralization cycle to allow the flue gas to slowly penetrate the blank.

[0003] Chinese patent application document CN116514476A discloses a high carbonization degree and high strength steel slag carbonized brick and its preparation method. The patent uses 99.99% CO2 gas, activator, inorganic porous material and inorganic adhesive to synergistically improve the carbonization effect and carbon fixation amount, but its ultra-long mineralization cycle and huge flue gas consumption further increase the cost of solid waste disposal, reduce the disposal efficiency, and seriously affect the production line capacity. Chinese patent application document CN113650132A discloses an artificial rock material suitable for negative temperature environment and its preparation method. The patent uses 99% concentration of CO2 gas to cure the blank for 24 hours at a temperature of -40℃ to 0℃, which effectively improves the compressive strength and carbonization degree of carbon mineralized artificial stone. However, the mineralization time in this technology is still relatively long, the economy is not ideal, and it does not pay attention to the problem of uniformity of carbon fixation inside and outside the carbon mineralized artificial stone.

[0004] Therefore, it is of great significance to develop a mineralization technology with short mineralization period, large carbon fixation amount, high carbon fixation uniformity, and high mechanical strength of carbon mineralized artificial stone. Summary of the invention

[0005] In order to solve the above technical problems, the first aspect of the present invention provides a carbon mineralized artificial stone based on solid waste, and the raw materials of the carbon mineralized artificial stone include: solid waste raw materials, aggregates, defoamers, water reducers, retarders and admixtures.

[0006] Preferably, the raw materials of the carbon mineralized artificial stone include, by weight: 39-125 parts of solid waste raw materials, 8-27 parts of aggregates, 0.1-0.5 parts of defoamers, 0.1-0.5 parts of water reducers, 0.1-1 parts of retarders and 2-15 parts of admixtures.

[0007] More preferably, the raw materials of the carbon mineralized artificial stone include: 51-112 parts of solid waste raw materials, 11-25 parts of aggregates, 0.1-0.3 parts of defoamers, 0.2-0.4 parts of water reducing agents, 0.3-0.7 parts of retarders and 4-11 parts of admixtures.

[0008] Furthermore, the solid waste raw material includes at least one of calcareous solid waste, siliceous and aluminum-based solid waste, and gel solid waste.

[0009] Preferably, the solid waste raw materials include calcareous solid waste, siliceous and aluminous solid waste and gel solid waste.

[0010] Furthermore, the calcareous solid waste is one or more of steel slag, magnesium slag, carbide slag, phosphorus slag, manganese slag, gypsum waste slag, purification ash, papermaking white mud, and chlor-alkali salt mud.

[0011] Furthermore, the siliceous and aluminous solid waste is one or more of fly ash, glass tailings, coal gasification slag, furnace slag, bottom ash, red mud, steel slag, and coal gangue.

[0012] Furthermore, the gel solid waste is one or more of industrial by-product waste cement, slag, limestone powder, desulfurized gypsum, iron tailings powder, metakaolin, and blast furnace slag.

[0013] Furthermore, the mass ratio of calcareous solid waste, siliceous and aluminum-silica solid waste and gel solid waste is (25-65):(9-40):(5-20).

[0014] Preferably, the mass ratio of calcareous solid waste, siliceous and aluminum-silica solid waste and gel solid waste is (29-62):(15-34):(7-16).

[0015] Furthermore, the amount of aggregate added accounts for 0-45% of the total mass of aggregate and solid waste raw materials, preferably 0-30%, and more preferably 5-25%.

[0016] Furthermore, the amount of calcium solid waste accounts for 20-80% of the total mass of aggregate and solid waste raw materials, preferably 30-70%.

[0017] Furthermore, the amount of silicoaluminous solid waste accounts for 1-45% of the total mass of aggregate and solid waste raw materials, preferably 5-30%.

[0018] Furthermore, the amount of gel solid waste accounts for 0-40% of the total mass of aggregate and solid waste raw materials, preferably 0-25%, and more preferably 5-20%.

[0019] Furthermore, the amount of the defoaming agent used accounts for 0.03-2% of the total mass of the aggregate and solid waste raw materials, preferably 0.1-0.5%.

[0020] Furthermore, the defoaming agent includes but is not limited to at least one of polyacrylamide, polyvinyl alcohol, silicone oil, and fatty alcohol.

[0021] Furthermore, the amount of water reducing agent used accounts for 0.05-3% of the total mass of aggregate and solid waste raw materials, preferably 0.1-0.5%.

[0022] Furthermore, the water reducer is selected from at least one of a polycarboxylic acid water reducer and a naphthalene water reducer.

[0023] Furthermore, the amount of retarder used accounts for 0.01-2% of the total mass of aggregate and solid waste raw materials, preferably 0.1-0.8%.

[0024] Furthermore, the retarder includes, but is not limited to, one or more of hydroxycarboxylate retarders, polyalkyl carbohydrate retarders, and inorganic compound retarders.

[0025] Furthermore, the raw materials for preparing the additive include aminoguanidine compounds, silane coupling agents and diacid compounds.

[0026] Furthermore, the aminoguanidine compound is a combination of one or more of aminoguanidine bicarbonate, aminoguanidine hydrochloride, and diaminoguanidine hydrochloride.

[0027] Furthermore, the silane coupling agent is a silane coupling agent having an epoxy group.

[0028] Furthermore, the silane coupling agent is a combination of one or more of KH560, hydrosil 2627 and hydrosil 2926.

[0029] Furthermore, the diacid compound is a combination of one or more of acetone dicarboxylic acid and α-ketoglutaric acid.

[0030] Furthermore, the mass ratio of the aminoguanidine compound, the silane coupling agent and the diacid compound is 1:(1-8):(0.1-5).

[0031] Furthermore, the mass ratio of the aminoguanidine compound, the silane coupling agent and the diacid compound is 1:(2-6):(0.4-4).

[0032] Furthermore, the preparation steps of the admixture include:

[0033] (1) adding an aminoguanidine compound and a silane coupling agent to a solvent and stirring for 12-48 hours to obtain a mixture A;

[0034] (2) The mixture A and the diacid compound are fully mixed to obtain an admixture.

[0035] The solvent in step (1) is not particularly limited, as long as it can achieve the purpose of dissolution; for example, water, alcohol-water solution.

[0036] In the admixture, the amino group on the aminoguanidine compound is bonded with the epoxy group on the silane coupling agent to obtain a mixture A, and after adding the diacid compound, the admixture is obtained. The mixture A can not only have a good binding force with the solid waste and aggregate in the system, but also optimize the pore structure and improve the performance of the green body. At the same time, in the mineralization environment with CO2 and water, the aminoguanidine compound in the mixture A reacts with the diacid compound to generate guanidine bicarbonate, and then produces bicarbonate ions, which form precipitation with the divalent metal cations in the system, optimize the green body pore structure, improve the mechanical strength of the product, and achieve a higher carbon absorption capacity; in addition, the diacid compound can also undergo a decarboxylation reaction to generate CO2, realize internal mineralization, optimize the degree of mineralization, and further improve the mechanical strength and carbon fixation rate of carbon mineralized products.

[0037] The second aspect of the present invention provides a process for preparing carbon mineralized artificial stone based on solid waste, comprising the following steps:

[0038] S1. Pretreatment of solid waste raw materials: After iron removal, powdering and screening, the solid waste raw materials are stored in a storage hopper for standby use;

[0039] S2. Mixing and mixing ingredients: After the solid waste raw materials, aggregates, defoamers, water reducers, retarders and admixtures are fully mixed to obtain a mixture, water is added, and the mixture is fully mixed to obtain a wet material;

[0040] S3, digestion, crushing and mixing: the wet material is transferred to the digestion system, digested, crushed, screened, and entered the next stage;

[0041] S4, automatic fabric distribution: the automatic fabric distribution system realizes uniform and parameter-controllable fabric distribution;

[0042] S5, compression molding process: the wet material is pressed into green billets in batches and enters the next stage;

[0043] S6, pre-mineralization treatment: using low-concentration flue gas to pre-mineralize the green body;

[0044] S7, CO2 graded mineralization treatment: using medium and high concentration CO2 gas to graded mineralize the pre-mineralized green body to obtain mineralized products;

[0045] S8, polishing and grinding treatment: grinding and polishing the mineralized product to obtain a finished product;

[0046] S9, fully automatic packaging.

[0047] The specific process is as follows:

[0048] Furthermore, step S1 includes:

[0049] Use a vibrating feeder to ball-mill and screen the solid waste raw materials from the raw material yard in turn, control the particle size of the raw materials to 100-200 mesh, and store them in a temporary storage warehouse.

[0050] Furthermore, step S2 includes:

[0051] The pre-treated solid waste raw materials, aggregates, defoamers, water reducing agents, retarder and admixtures are mixed according to the mixing ratio and stirred twice. During the first stirring, the above components are mixed and stirred thoroughly to obtain a mixture; during the second stirring, water is added to the mixture and stirred thoroughly to obtain a wet material.

[0052] Furthermore, in step S2, the average particle size of the solid waste aggregate is 0.15-4.75 mm.

[0053] Furthermore, in step S2, the amount of water used is 5-60% of the mass of the mixture.

[0054] Furthermore, step S3 includes:

[0055] The wet material obtained by stirring in step S2 is transferred to the digestion system for digestion for 0.5-2 hours, and then discharged after crushing and stirring; the material is sieved when discharged, and the material that does not meet the particle size requirements is returned to the powder mixing system for re-crushing, and the qualified material that meets the particle size requirements is sent to the next stage for processing by a belt conveyor.

[0056] Furthermore, step S4 includes:

[0057] The material is evenly laid on the conveyor belt using an automatic material distribution system. The automatic material distribution system is mainly composed of a distribution machine body, a rotary device, a hydraulic system, a pipe device, etc. Specifically, the finished product feeding system first transports the digested powder mixed material to the distribution machine feeding system, and mechanically inputs the material to the wheel shaft of the distribution machine; then the wheel system pulls the material into the machine to form a separate fiber layer, and adjusts the angle to create fabrics with different textures; then the hydraulic system repeatedly pushes and stretches downward to make the distribution more uniform and stable. The material after distribution is transported to the next process. During automatic distribution, the speed of the conveyor belt is coordinated with the distribution speed to ensure that the material will not accumulate or scatter due to speed mismatch.

[0058] Furthermore, step S5 includes: a conveyor belt transports the evenly laid raw materials to a pressing and molding area, and a ceramic press presses the wet materials to form green bodies, and batches are formed each time. After pressing, the green bodies are transferred to the next step.

[0059] Furthermore, step S6 includes: placing the green body into a mineralization reaction device, and introducing low-concentration flue gas for pre-mineralization.

[0060] Furthermore, in step S6, the low-concentration flue gas may come from at least one of: coal chemical exhaust gas, power plant flue gas, lime kiln flue gas, steel plant blast furnace, converter, refining furnace, petrochemical exhaust gas, waste incineration plant flue gas, cement plant flue gas, and aluminum smelter flue gas.

[0061] Further, in step S6, the volume fraction of CO2 in the low-concentration flue gas is 2-55%, preferably 3-45%, and more preferably 4-30%. The present invention directly uses industrial direct exhaust gas or recycles the residual flue gas of the mineralization reaction to pre-mineralize the green body in the early stage of mineralization, generates calcium carbonate nuclei while promoting the early strength of the green body, and further stimulates the mineralization efficiency of the rear end based on the nucleation effect, but it is necessary to control the concentration of CO2 during the pre-mineralization process to avoid rapid mineralization of the outer layer of the green body when the concentration is too high, resulting in the formation of a dense calcium carbonate and silica gel layer on the outer layer, affecting the degree of flue gas diffusion during the gradual mineralization of the rear end layer, but causing internal and external stratification problems.

[0062] Furthermore, in step S6, the pre-mineralization temperature is 10-90° C., and the mineralization time is 0.5-10 h.

[0063] Preferably, in step S6, the pre-mineralization temperature is 20-60° C., and the mineralization time is 1-8 h.

[0064] Furthermore, step S7 includes: after step S6 is completed, introducing medium-high concentration CO2 gas for graded mineralization.

[0065] Furthermore, in step S7, medium and high concentration CO2 gas may come from: coal chemical exhaust gas, power plant flue gas, lime kiln flue gas, steel plant blast furnace, converter, refining furnace, petrochemical exhaust gas, waste incineration plant flue gas, cement plant flue gas, aluminum smelter flue gas, and at least one of commercially available CO2 gas.

[0066] Furthermore, in step S7, the volume fraction of CO2 in the medium-high concentration CO2 gas is 8-99.99%, preferably 30-99.99%, and more preferably 55-99.99%.

[0067] Further, in step S7, the graded mineralization is as follows:

[0068] Primary mineralization: mineralization pressure is 0.05-0.5MPa, mineralization temperature is 20-80℃, and mineralization time is 0.5-6h;

[0069] Secondary mineralization: mineralization pressure is 0.2-0.6MPa, mineralization temperature is 40-120℃, and mineralization time is 0.5-6h;

[0070] Level 3 mineralization: mineralization pressure is 0.4-1.0MPa, mineralization temperature is 60-120℃, and mineralization time is 0.5-6h;

[0071] Level 4 mineralization: mineralization pressure is 0.4-1.5MPa, mineralization temperature is 60-120℃, and mineralization time is 0.5-6h.

[0072] The present invention adopts a graded mineralization gradient layer-by-layer curing system to ensure that each stage of the mineralization reaction is in the optimal thermodynamic and kinetic process synergistic equilibrium state, and realizes the internal and external uniformity and sufficiency of the mineralization reaction while significantly shortening the mineralization cycle. During the layer-by-layer mineralization curing process, the pressure affects the CO2 kinetic process at each stage; too low mineralization pressure causes the temperature rise rate in the device to slow down, and at the same time, the amount of CO2 molecules and water dissolved in the body is reduced, that is, the diffusion efficiency of the flue gas to the inside of the product decreases. At this time, if it is in a high temperature environment, the thermodynamics and kinetics are unbalanced, and the mineralization reaction occurs in large quantities on the surface of the body, resulting in an obvious "stratification" phenomenon, but too high a mineralization pressure causes the free calcium ions to combine quickly with the calcium carbonate ions, hindering the subsequent diffusion of the CO2 molecules, and also leading to the problem of insufficient internal mineralization reaction. Therefore, it is necessary to optimize the mineralization pressure and mineralization temperature, effectively promote the penetration and diffusion of CO2 inside the matrix during the mineralization process, ensure that the molecular diffusion and chemical bonding in each reaction stage of the mineralization are in the optimal thermodynamic and kinetic process synergistic equilibrium state, and realize the uniformity and sufficiency of the mineralization reaction.

[0073] Preferably, in step S7, the graded mineralization is as follows:

[0074] Primary mineralization: mineralization pressure is 0.1-0.3MPa, mineralization temperature is 20-60℃, and mineralization time is 0.5-4h.

[0075] Secondary mineralization: mineralization pressure is 0.3-0.5MPa, mineralization temperature is 40-100℃, and mineralization time is 0.5-4h.

[0076] Level 3 mineralization: mineralization pressure is 0.5-0.7MPa, mineralization temperature is 80-100℃, and mineralization time is 1-4h.

[0077] Level 4 mineralization: mineralization pressure is 0.5-0.7MPa, mineralization temperature is 80-100℃, and mineralization time is 1-4h.

[0078] Furthermore, in steps S6-S7, the humidity of the reaction environment is 40-99.9%, preferably 55-98%, and more preferably 60-95%.

[0079] Furthermore, step S8 includes: grinding the product after the mineralization reaction for multiple times, firstly performing rough grinding, then performing fine grinding, and then performing polishing to obtain a product with a smooth and bright surface.

[0080] Specifically, step S8 is as follows: after the mineralization reaction is completed, the blank is sent to a wide-band sander through a track for grinding, the polished artificial stone is sent to an automatic polishing machine via a belt, the polishing agent is evenly applied using a flexible polishing disc, the polishing intensity and speed are adjusted according to the different requirements of the artificial stone, and the artificial stone is finally polished to increase the smoothness and gloss of the surface.

[0081] Furthermore, step S9 includes: transporting the products after the polishing and grinding process to a fully automatic packaging machine via a track to achieve fully automatic pallet-free packaging.

[0082] The packaged finished products are transported to the finished product yard by forklift for sale.

[0083] Beneficial Effects

[0084] 1. The present invention uses solid waste raw materials, aggregates, defoamers, water reducers, retarders and admixtures as raw materials to prepare carbon mineralized artificial stones. The admixtures are synthesized using aminoguanidine compounds, silane coupling agents and diacid compounds as raw materials. The introduction of admixtures can not only generate pore-filling substances and CO2 gas in the system, optimize the pore structure and achieve internal mineralization, but also enhance the binding force between the components in the system, thereby improving the carbonization degree, carbon fixation rate and mechanical strength of the carbon mineralization product. The artificial stone prepared by the present invention has a high degree of carbonization and excellent mechanical strength, which can not only help the resource utilization of solid waste, but also achieve effective carbon absorption.

[0085] 2. The present application sets up a pre-mineralization process, fully utilizing low-concentration CO2 flue gas to promote the formation of early strength of the green body, providing seeds for subsequent graded mineralization reactions, and promoting the penetration and diffusion of CO2 inside the matrix during the mineralization process, thereby ensuring that the molecular diffusion and chemical bonding in each reaction stage of the mineralization are in the optimal thermodynamic and kinetic process coordinated equilibrium state, thereby achieving uniformity and sufficiency of the mineralization reaction;

[0086] 3. The present application adopts a gradual mineralization curing method, which can ensure that the green body is in the optimal synergistic balance of mineralization thermodynamics and kinetics at each stage of the mineralization reaction, so that the leaching rate and leaching rate of calcium ions from the inside of the green body to the outside are optimal, and the diffusion of CO2 gas molecules inside the green body structure is promoted, the mineralization sufficiency is enhanced, the green body mineralization is uniform inside and outside, and the layered distribution and superposition of the product calcium silicate crystals are promoted;

[0087] 4. The method of the present application effectively solves the problems in the existing mineralization process, such as large restriction on CO2 concentration, insufficient reaction, different mineralization degrees inside and outside the blank, and long mineralization cycle. The prepared carbon mineralized artificial stone has excellent mechanical strength, high carbon fixation rate and uniform carbon fixation degree in the inner and outer layers. DETAILED DESCRIPTION

[0088] The invention provides a carbon mineralized artificial stone based on solid waste, and the preparation raw materials thereof include solid waste raw materials, aggregates, defoamers, water reducing agents, retarder and admixtures.

[0089] In some embodiments, the raw materials of carbon mineralized artificial stone include, by weight: 39-125 parts of solid waste raw materials, 8-27 parts of aggregates, 0.1-0.5 parts of defoaming agents, 0.1-0.5 parts of water reducing agents, 0.1-1 parts of retarders, and 2-15 parts of admixtures.

[0090] In some embodiments, the raw materials of carbon mineralized artificial stone include: 51-112 parts of solid waste raw materials, 11-25 parts of aggregates, 0.1-0.3 parts of defoaming agent, 0.2-0.4 parts of water reducing agent, 0.3-0.7 parts of retarder and 4-11 parts of admixture.

[0091] In some embodiments, the raw materials for preparing the additive include aminoguanidine compounds, silane coupling agents and diacid compounds.

[0092] In some embodiments, the aminoguanidine compound is a combination of one or more of aminoguanidine bicarbonate, aminoguanidine hydrochloride, and diaminoguanidine hydrochloride.

[0093] In some embodiments, the silane coupling agent is a silane coupling agent having an epoxy group.

[0094] In some embodiments, the silane coupling agent is a combination of one or more of KH560, hydrosil 2627, and hydrosil 2926.

[0095] In some embodiments, the diacid compound is a combination of one or more of acetone dicarboxylic acid and α-ketoglutaric acid.

[0096] In some embodiments, the mass ratio of the aminoguanidine compound, the silane coupling agent and the diacid compound is 1:(1-8):(0.1-5).

[0097] In some embodiments, the mass ratio of the aminoguanidine compound, the silane coupling agent and the diacid compound is 1:(2-6):(0.4-4).

[0098] In some embodiments, the steps of preparing the admixture include:

[0099] (1) adding an aminoguanidine compound and a silane coupling agent to a solvent and stirring for 12-48 hours to obtain a mixture A;

[0100] (2) The mixture A and the diacid compound are fully mixed to obtain an admixture.

[0101] In some embodiments, the solvent in step (1) is not particularly limited, as long as it can achieve the purpose of dissolution; for example: water, alcohol-water solution.

[0102] The preparation process of the carbon mineralized artificial stone comprises the following steps:

[0103] S1. Pretreatment of solid waste raw materials: After iron removal, powdering and screening, the solid waste raw materials are stored in a storage hopper for standby use;

[0104] S2. Mixing and mixing ingredients: After the solid waste raw materials, aggregates, defoamers, water reducers, retarders and admixtures are fully mixed to obtain a mixture, water is added, and the mixture is fully mixed to obtain a wet material;

[0105] S3, digestion, crushing and mixing: the wet material is transferred to the digestion system, digested, crushed, screened, and entered the next stage;

[0106] S4, automatic material distribution: the wet material is transferred to the digestion system, digested, crushed, screened, and then enters the next stage;

[0107] S5, compression molding process: the wet material is pressed into green billets in batches and enters the next stage;

[0108] S6, pre-mineralization treatment: using low-concentration flue gas to pre-mineralize the green body;

[0109] S7, CO2 graded mineralization treatment: using medium and high concentration CO2 gas to graded mineralize the pre-mineralized green body to obtain mineralized products;

[0110] S8, polishing and grinding treatment: grinding and polishing the mineralized product to obtain a finished product;

[0111] S9, fully automatic packaging.

[0112] In some embodiments, step S1 includes:

[0113] Use a vibrating feeder to ball-mill and screen the solid waste raw materials from the raw material yard in turn, control the particle size of the raw materials to 100-200 mesh, and store them in a temporary storage warehouse.

[0114] In some embodiments, step S2 comprises:

[0115] The pre-treated solid waste raw materials, aggregates, defoamers, water reducing agents, retarder and admixtures are mixed according to the mixing ratio and stirred twice. During the first stirring, the above components are mixed and stirred thoroughly to obtain a mixture; during the second stirring, water is added to the mixture and stirred thoroughly to obtain a wet material.

[0116] In some embodiments, the solid waste raw material includes at least one of calcareous solid waste, siliceous and aluminum-based solid waste, and gel solid waste.

[0117] In some embodiments, the solid waste raw materials include calcareous solid waste, siliceous and aluminous solid waste, and gelatinous solid waste.

[0118] In some embodiments, the calcareous solid waste is one or more of steel slag, magnesium slag, carbide slag, phosphorus slag, manganese slag, gypsum waste slag, purification ash, papermaking white mud, and chlor-alkali salt mud.

[0119] In some embodiments, the siliceous and aluminous solid waste is one or more of fly ash, glass tailings, coal gasification slag, furnace slag, bottom ash, red mud, steel slag, and coal gangue.

[0120] In some embodiments, the gel solid waste is one or more of industrial by-product waste cement, slag, limestone powder, desulfurized gypsum, iron tailings powder, metakaolin, and blast furnace slag.

[0121] In some embodiments, in the solid waste raw materials, the mass ratio of calcareous solid waste, siliceous and aluminum-based solid waste and gel solid waste is (25-65):(9-40):(5-20).

[0122] In some embodiments, in the solid waste raw materials, the mass ratio of calcareous solid waste, siliceous and aluminum-based solid waste and gel solid waste is (29-62):(15-34):(7-16).

[0123] In some embodiments, the average particle size of the solid waste aggregate is 0.15-4.75 mm.

[0124] In some embodiments, the amount of aggregate added is 0-45% of the total mass of the aggregate and solid waste raw materials, preferably 0-30%, and more preferably 5-25%.

[0125] In some embodiments, the amount of calcareous solid waste accounts for 20-80% of the total mass of aggregate and solid waste raw materials, preferably 30-70%.

[0126] In some embodiments, the amount of silicoaluminous solid waste is 1-45% of the total mass of aggregate and solid waste raw materials, preferably 5-30%.

[0127] In some embodiments, the amount of gel solid waste is 0-40% of the total mass of aggregate and solid waste raw materials, preferably 0-25%, and more preferably 5-20%.

[0128] In some embodiments, the amount of defoamer used is 0.03-2%, preferably 0.1-0.5%, of the total mass of the aggregate and solid waste raw materials.

[0129] In some embodiments, the defoaming agent includes but is not limited to at least one of polyacrylamide, polyvinyl alcohol, silicone oil, and fatty alcohol.

[0130] In some embodiments, the amount of water reducing agent used is 0.05-3% of the total mass of the aggregate and solid waste raw materials, preferably 0.1-0.5%.

[0131] In some embodiments, the water reducer is selected from at least one of a polycarboxylate water reducer and a naphthalene water reducer.

[0132] In some embodiments, the amount of retarder used is 0.01-2%, preferably 0.1-0.8%, of the total mass of aggregate and solid waste raw materials.

[0133] In some embodiments, the retarder includes, but is not limited to, one or more of a hydroxycarboxylate type retarder, a polyalkyl carbohydrate type retarder, and an inorganic compound type retarder.

[0134] In some embodiments, in step S2, the amount of water used is 5-60% of the mass of the mixture.

[0135] In some embodiments, step S3 includes: transferring the wet material obtained by stirring in step S2 to a digestion system, digesting for 0.5-2 hours, and then discharging the material after crushing and stirring; screening the material when discharging, returning the material that does not meet the particle size requirements to the powder mixing system for re-crushing, and sending the qualified material that meets the particle size requirements to the next stage for processing by a belt conveyor.

[0136] In some embodiments, step S4 includes:

[0137] The material is evenly laid on the conveyor belt using an automatic material distribution system. The automatic material distribution system is mainly composed of a distribution machine body, a rotary device, a hydraulic system, a pipe device, etc. Specifically, the finished product feeding system first transports the digested powder mixed material to the distribution machine feeding system, and mechanically inputs the material into the wheel shaft of the distribution machine. The wheel system then pulls the material into the machine to form a separate fiber layer. By adjusting the angle, fabrics with different textures can be created. The hydraulic system then repeatedly pushes and stretches downward to make the fabric more uniform and stable. The material after distribution is transported to the next process. During automatic distribution, the speed of the conveyor belt is coordinated with the distribution speed to ensure that the material will not accumulate or scatter due to speed mismatch.

[0138] In some embodiments, step S5 includes: a conveyor belt transports the evenly laid raw materials to a pressing and molding area, and a ceramic press presses the wet materials to form green bodies, and batches are formed each time. After pressing, the green bodies are transferred to the next step.

[0139] In some embodiments, step S6 includes: placing the green body into a mineralization reaction device, and introducing low-concentration flue gas for pre-mineralization.

[0140] In some embodiments, in step S6, the low-concentration flue gas may come from at least one of: coal chemical exhaust gas, power plant flue gas, lime kiln flue gas, steel plant blast furnace, converter, refining furnace, petrochemical exhaust gas, waste incineration plant flue gas, cement plant flue gas, and aluminum smelter flue gas.

[0141] In some embodiments, in step S6, the volume fraction of CO2 in the low-concentration flue gas is 2-55%, preferably 3-45%, and more preferably 4-30%.

[0142] In some embodiments, in step S6, the pre-mineralization temperature is 10-90° C., and the mineralization time is 0.5-10 h.

[0143] In some embodiments, in step S6, the pre-mineralization temperature is 20-60° C., and the mineralization time is 1-8 h.

[0144] In some embodiments, step S7 includes: after step S6 is completed, medium-high concentration CO2 gas is introduced to perform graded mineralization.

[0145] In some embodiments, in step S7, medium to high concentration CO2 gas may come from: coal chemical exhaust gas, power plant flue gas, lime kiln flue gas, steel plant blast furnace, converter, refining furnace, petrochemical exhaust gas, waste incineration plant flue gas, cement plant flue gas, aluminum smelter flue gas, and at least one of commercially available CO2 gas.

[0146] In some embodiments, in step S7, the volume fraction of CO2 in the medium-high concentration CO2 gas is 8-99.99%, preferably 30-99.99%, and more preferably 55-99.99%.

[0147] In some embodiments, in step S7, the graded mineralization is as follows:

[0148] Primary mineralization: mineralization pressure is 0.05-0.5MPa, mineralization temperature is 20-80℃, and mineralization time is 0.5-6h;

[0149] Secondary mineralization: mineralization pressure is 0.2-0.6MPa, mineralization temperature is 40-120℃, and mineralization time is 0.5-6h;

[0150] Level 3 mineralization: mineralization pressure is 0.4-1.0MPa, mineralization temperature is 60-120℃, and mineralization time is 0.5-6h;

[0151] Level 4 mineralization: mineralization pressure is 0.4-1.5MPa, mineralization temperature is 60-120℃, and mineralization time is 0.5-6h.

[0152] In some embodiments, in step S7, the graded mineralization is as follows:

[0153] Primary mineralization: mineralization pressure is 0.1-0.3MPa, mineralization temperature is 20-60℃, and mineralization time is 0.5-4h.

[0154] Secondary mineralization: mineralization pressure is 0.3-0.5MPa, mineralization temperature is 40-100℃, and mineralization time is 0.5-4h.

[0155] Level 3 mineralization: mineralization pressure is 0.5-0.7MPa, mineralization temperature is 80-100℃, and mineralization time is 1-4h.

[0156] Level 4 mineralization: mineralization pressure is 0.5-0.7MPa, mineralization temperature is 80-100℃, and mineralization time is 1-4h.

[0157] In some embodiments, in steps S6-S7, the humidity of the reaction environment is 40-99.9%, preferably 55-98%, and more preferably 60-95%.

[0158] In some embodiments, step S8 includes: grinding the product after the mineralization reaction is completed multiple times, first rough grinding, then fine grinding, and then polishing to obtain a product with a smooth and bright surface.

[0159] In some embodiments, step S8 is: after the mineralization reaction is completed, the blank is sent to a wide-band sander for polishing via a track, and the polished artificial stone is sent to an automatic polishing machine via a belt, and the polishing agent is evenly applied using a flexible polishing disc. The polishing intensity and speed are adjusted according to the different requirements of the artificial stone, and the artificial stone is finally polished to increase the smoothness and gloss of the surface.

[0160] In some embodiments, step S9 includes: transporting the finished products after the polishing and grinding process to a fully automatic packaging machine via a track to achieve fully automatic pallet-free packaging. The packaged finished products are transported to the finished product yard by a forklift for sale.

[0161] Example 1

[0162] In a first aspect, the present embodiment provides a carbon mineralized artificial stone based on solid waste, and the preparation process thereof comprises the following steps:

[0163] S1. Pretreatment of solid waste raw materials: Use a vibrating feeder to ball mill and screen the solid waste raw materials from the raw material yard (steel slag, glass tailings, fly ash, waste cement), control the raw material particle size to 100-200 mesh, and store them in a temporary warehouse. Among them, different solid waste raw materials are pretreated separately and stored separately after pretreatment.

[0164] S2, batching, stirring and mixing: First, each raw material is sent to a measuring hopper through a respective belt conveyor, and the raw materials in the storage hopper are sent to a measuring hopper through a respective belt conveyor for measurement, and then conveyed to a mixer by a belt conveyor for full mixing to obtain a mixture, wherein the raw material ratio is: 81.1 parts of solid waste raw materials (45 parts of steel slag (200 mesh), 9.5 parts of glass tailings (200 mesh), 15 parts of fly ash (150 mesh), 11.6 parts of waste cement (200 mesh)), 18 parts of waste concrete aggregate (particle size range is 2.1 mm), 0.2 parts of polyvinyl alcohol defoamer, 0.3 parts of polycarboxylic acid water reducer, 0.5 parts of sodium gluconate, and 7.5 parts of admixture. The mixture is conveyed to the storage hopper of another mixer by a belt, and then conveyed to the mixer by a screw conveyor, and then a water metering scale introduces 25 parts of water into the mixer for full mixing to obtain a wet material.

[0165] The preparation steps of the admixture include:

[0166] (1) adding 5 parts of diaminoguanidine hydrochloride and 19 parts of a silane coupling agent to a 60% ethanol aqueous solution (the concentration of the silane coupling agent is 3%), stirring for 36 hours, and then removing the solvent by rotary evaporation to obtain a mixture A;

[0167] (2) Mixture A and 5 parts of acetone dicarboxylic acid are thoroughly mixed to obtain an admixture.

[0168] S3, digestion, crushing and mixing: the wet material after stirring in step S2 is sent to the digestion system through a sealed belt. The digestion time is 1 hour. The digested mixture is crushed and stirred by a strong powder mixing system, and then discharged through a pneumatic double-sided plow discharger, and sent to the finished product storage system and feeding system by a belt conveyor, waiting for the next step.

[0169] S4, automatic material distribution: Use the automatic material distribution system to evenly distribute the materials on the conveyor belt. Specifically, the finished product feeding system first transports the digested powder mixed materials from the finished product storage bin to the material distribution machine feeding system through the feeding conveyor belt, and then inputs the materials into the wheel shaft of the material distribution machine through the conveying device, and then the wheel system pulls the materials into the machine for distribution; then the hydraulic system repeatedly pushes down and stretches to make the distribution more uniform and stable. The materials after distribution are transported to the next process.

[0170] S5, Compression molding process: The conveyor belt transports the evenly laid raw materials to the compression molding area. The materials in the mold on the belt are pressed by the ceramic press to become green billets (batch molding each time). The robot suction cup is used to suck up and transfer the green billets from the mold, and then the fully automatic stacking robot is placed on the special trolley for mineralization reaction.

[0171] S6, Pre-mineralization treatment: The special trolley for mineralization reaction drives into the artificial stone pre-mineralization plant along the predetermined route. The humidifier and heating device are controlled by the integrated control system in the plant to always keep the environment in the pre-mineralization warehouse at a constant temperature and humidity. The special trolley for mineralization reaction loaded with embryos stops in the pre-mineralization plant, and 20% volume concentration of CO2 flue gas is introduced. Pre-mineralization is carried out for 4 hours at 60℃ and 90% humidity to obtain pre-mineralized embryos: it drives out and enters the next section.

[0172] S7, CO2 graded mineralization treatment: After the pre-mineralization is completed, the special trolley for mineralization reaction will send the embryo into the CO2 mineralization reactor, close the reactor, and fill a small amount of water vapor at the reactor mouth for 30 seconds to seal the reactor. After that, the flue gas containing CO2 is input from the gas tank until the test partial pressure condition is reached. Since CO2 is continuously consumed in the mineralization reaction, the CO2 partial pressure will drop accordingly, so it is necessary to continuously replenish the gas to ensure that the CO2 partial pressure is maintained within a certain range of the specified test pressure during the entire maintenance process for graded mineralization. After the mineralization is completed, the remaining gas in the kettle is introduced into the next kettle to achieve pressure equalization control and recover part of the remaining CO2 to ensure the overall reaction absorption rate of the mineralization reaction system.

[0173] Specifically, CO2 gas with a volume concentration of 99.9% was introduced into the mineralization reactor for four-stage mineralization. The humidity of the first to fourth stages of mineralization was 90%. The mineralization conditions of each stage were as follows:

[0174] (1) Primary mineralization: adjust the mineralization pressure to 0.2 MPa and the mineralization temperature to 40°C. After the above conditions are met, mineralization maintenance is performed for 1 hour;

[0175] (2) Secondary mineralization: adjust the mineralization pressure to 0.4 MPa and the mineralization temperature to 60°C. After the above conditions are met, mineralization maintenance is performed for 1 hour;

[0176] (3) Level 3 mineralization: adjust the mineralization pressure to 0.6 MPa and the mineralization temperature to 80 °C. After the above conditions are met, mineralization maintenance is performed for 2 h.

[0177] (4) Level 4 mineralization: Maintain the mineralization conditions at the end of level 3 mineralization and continue mineralization maintenance for 2 hours; after the reaction is completed, close the CO2 inlet valve and wait until the temperature in the device drops to room temperature to obtain the mineralized product.

[0178] S8. Polishing and grinding: After the mineralization reaction is completed, it is sent to the wide belt sander for grinding through the track. The polished artificial stone is sent to the automatic polishing machine through the belt, and the polishing agent is evenly applied using a flexible polishing disc to perform the final polishing treatment on the artificial stone to increase the smoothness and gloss of the surface.

[0179] S9. Fully automatic packaging: The finished products after polishing and grinding are the finished products. They are transported to the fully automatic packaging machine through the track to achieve fully automatic pallet-free packaging. The packaged finished products are transported to the finished product yard for sale by forklifts, and the special trolley for mineralization reaction returns to the molding section for reuse.

[0180] Example 2

[0181] The carbon mineralized artificial stone based on solid waste provided in this embodiment is basically the same as that in embodiment 1, except that:

[0182] The conditions for S6 pre-mineralization are: the concentration of carbon dioxide in the flue gas is 10%, the temperature is 80°C, the humidity is 85%, and the time is 6 hours.

[0183] The S7 graded mineralization conditions are: first-level mineralization pressure is 0.3MPa, temperature is 60℃, and time is 0.5h; second-level mineralization pressure is 0.5MPa, temperature is 80℃, and time is 1h; third-level mineralization pressure is 0.7MPa, temperature is 100℃, and time is 1h; fourth-level mineralization pressure is 0.7MPa, temperature is 100℃, and time is 2h.

[0184] The formula of the mixture is: by weight, 29.5 parts of steel slag (100 mesh), 6.2 parts of glass tailings (200 mesh), 9.8 parts of fly ash (150 mesh), 7.6 parts of waste cement (200 mesh), 11.8 parts of waste concrete aggregate (average particle size of 1 mm), 0.13 parts of polyvinyl alcohol defoamer, 0.2 parts of polycarboxylic acid water reducer, 0.3 parts of sodium gluconate, and 4.9 parts of admixture. The water in the wet material is 16.5 parts.

[0185] The preparation steps of the admixture include:

[0186] (1) 2 parts of diaminoguanidine hydrochloride and 4 parts of KH560 were added to a 60% ethanol aqueous solution (the concentration of KH560 was 3%), stirred for 15 hours, and then the solvent was removed by rotary evaporation to obtain a mixture A;

[0187] (2) Mixture A and 8 parts of acetone dicarboxylic acid are thoroughly mixed to obtain an admixture.

[0188] Example 3

[0189] The carbon mineralized artificial stone based on solid waste provided in this embodiment is basically the same as that in embodiment 1, except that:

[0190] The conditions for S6 pre-mineralization are: the concentration of carbon dioxide in the flue gas is 25%, the temperature is 20°C, the humidity is 95%, and the time is 2h.

[0191] The S7 graded mineralization conditions are: first-level mineralization pressure is 0.1MPa, temperature is 20℃, and time is 4h; second-level mineralization pressure is 0.3MPa, temperature is 40℃, and time is 4h; third-level mineralization pressure is 0.5MPa, temperature is 80℃, and time is 4h; fourth-level mineralization pressure is 0.5MPa, temperature is 80℃, and time is 4h.

[0192] The formula of the mixture is: by weight, 62 parts of steel slag (300 mesh), 13 parts of glass tailings (400 mesh), 20.5 parts of fly ash (400 mesh), 16 parts of waste cement (500 mesh), 24.6 parts of waste concrete aggregate (average particle size of 3 mm), 0.3 parts of polyvinyl alcohol defoamer, 0.4 parts of polycarboxylic acid water reducer, 0.7 parts of sodium gluconate, and 10.3 parts of admixture.

[0193] The preparation steps of the admixture include:

[0194] (1) 7 parts of diaminoguanidine hydrochloride and 39 parts of KH560 were added to a 60% ethanol aqueous solution (the concentration of KH560 was 3%), stirred for 40 hours, and then the solvent was removed by rotary evaporation to obtain a mixture A;

[0195] (2) Mixture A and 3 parts of acetone dicarboxylic acid are thoroughly mixed to obtain an admixture.

[0196] Example 4

[0197] The carbon mineralized artificial stone based on solid waste provided in this embodiment is basically the same as that in embodiment 3, except that:

[0198] The preparation steps of the admixture include:

[0199] (1) 7 parts of diaminoguanidine hydrochloride and 49 parts of KH560 were added to a 60% ethanol aqueous solution (the concentration of KH560 was 3%), stirred for 40 hours, and then the solvent was removed by rotary evaporation to obtain a mixture A;

[0200] (2) Mixture A and 3 parts of acetone dicarboxylic acid are thoroughly mixed to obtain an admixture.

[0201] Example 5

[0202] The carbon mineralized artificial stone based on solid waste provided in this embodiment is basically the same as that in embodiment 3, except that:

[0203] The preparation steps of the admixture include:

[0204] (1) adding 7 parts of diaminoguanidine hydrochloride and 39 parts of silane coupling agent to a 60% ethanol aqueous solution (KH560 concentration is 3%), stirring for 40 hours, and then removing the solvent by rotary evaporation to obtain a mixture A;

[0205] (2) Mixture A and 30 parts of acetone dicarboxylic acid are fully mixed to obtain an admixture.

[0206] Example 6

[0207] The carbon mineralized artificial stone based on solid waste provided in this embodiment is basically the same as that in embodiment 3, except that:

[0208] The preparation steps of the admixture include:

[0209] (1) 7 parts of diaminoguanidine hydrochloride and 39 parts of KH560 were added to a 60% ethanol aqueous solution (the concentration of KH560 was 3%), stirred for 40 hours, and then the solvent was removed by rotary evaporation to obtain a mixture A;

[0210] (2) Mixture A and 1.4 parts of acetone dicarboxylic acid were thoroughly mixed to obtain an admixture.

[0211] Example 7

[0212] The carbon mineralized artificial stone based on solid waste provided in this embodiment is basically the same as that in embodiment 3, except that:

[0213] The preparation steps of the admixture include: uniformly mixing 7 parts of diaminoguanidine hydrochloride, 39 parts of KH560 and 3 parts of acetone dicarboxylic acid to obtain the admixture.

[0214] Comparative Example 1

[0215] This comparative example provides a carbon mineralized artificial stone based on solid waste, which is basically the same as Example 3, except that:

[0216] The preparation steps of the admixture are as follows: 39 parts of KH560 and 3 parts of acetone dicarboxylic acid are fully mixed to obtain the admixture.

[0217] Comparative Example 2

[0218] This comparative example provides a carbon mineralized artificial stone based on solid waste, which is basically the same as Example 3, except that:

[0219] The preparation steps of the admixture include: adding 7 parts of diaminoguanidine hydrochloride and 39 parts of KH560 into a 60% ethanol aqueous solution (the concentration of KH560 is 3%), stirring for 40 hours, and then removing the solvent by rotary evaporation to obtain the admixture.

[0220] Performance testing method:

[0221] The test pieces formed according to the above-mentioned embodiments and comparative examples, the preparation methods and the curing system were subjected to compressive strength tests and flexural strength tests in accordance with the relevant requirements of GB / T50081-2019. The carbon fixation rates inside and outside the test pieces were tested by thermogravimetric analysis (TG). The 1-3mm surface of the product was uniformly taken as the outer carbon fixation rate test sample, and the 1-3mm center of the product was taken as the inner carbon fixation rate test sample. The arithmetic mean of multi-point sampling was used as the final data. The final results are summarized in Table 1.

[0222] Performance test results:

[0223] Table 1

[0224] Compressive strength / MPa Flexural strength / MPa Internal carbon fixation rate / % External carbon fixation rate / % Example 1 97.6 23.3 16.3 18.4 Example 2 94.5 22.9 17.4 18.6 Example 3 93.2 22.4 15.7 18.3 Example 4 85.3 21.5 14.5 18.0 Example 5 84.5 20.6 16.8 18.4 Example 6 81.4 19.8 12.7 17.2 Example 7 89.1 22.0 15.7 18.1 Comparative Example 1 78.7 19.0 15.9 18.3 Comparative Example 2 76.4 18.3 8.4 16.7

[0225] Results: The compressive strength of the carbon mineralized artificial stone prepared in Examples 1-3 of the present application reached more than 93.2 MPa, the flexural strength reached more than 22.4 MPa, the degree of carbonization inside and outside was relatively uniform, the internal carbon fixation rate reached more than 15.7%, and the external carbon fixation rate reached more than 18.3%; This shows that the present application uses specific admixtures and solid waste and other raw materials to prepare carbon mineralized artificial stone, which can not only increase the carbon fixation amount of the mineralization reaction, thereby improving the product strength, and improving the mechanical strength and carbon fixation rate of carbon mineralized products.

[0226] Comparison of Example 3, Example 4 and Comparative Example 1 shows that: in the admixture, the amount of silane coupling agent increases, and diaminoguanidine hydrochloride and acetone dicarboxylic acid decrease relatively, which may lead to a decrease in the amount of mixture A and guanidine bicarbonate generated, and the internal pore optimization effect of the green body is limited, so the mechanical properties of the product are reduced; at the same time, the reduction in the amount of acetone dicarboxylic acid may also lead to a decrease in the amount of carbon dioxide released internally, and the internal mineralization effect of the green body is poor, which is not conducive to the improvement of the product's mechanical properties, internal carbon fixation rate and carbonization uniformity. When diaminoguanidine hydrochloride is not added, there is no mixture A and guanidine bicarbonate in the admixture that can optimize the green body pore structure, so the mechanical properties of the product are significantly reduced.

[0227] Comparative Example 3, Example 5-6 and Comparative Example 2 show that when the amount of acetone dicarboxylic acid added to the admixture is high, more CO2 gas may be generated during the mineralization and curing process of the green body. Although the internal carbon fixation rate and carbonization uniformity can be improved, the internal pore structure of the green body may be deteriorated. In addition, when the amount of acetone dicarboxylic acid added increases, the content of diaminoguanidine hydrochloride and silane coupling agent in the admixture is reduced, which may lead to a reduction in the amount of mixture A and guanidine bicarbonate generated, so the mechanical properties of the carbon mineralized artificial stone deteriorate, but the internal carbon fixation rate is significantly increased. When the amount of acetone dicarboxylic acid added to the admixture is low, the amount of guanidine bicarbonate generated is significantly reduced, which is not conducive to the coordinated mixture A to optimize the internal pore structure of the green body, and the amount of carbon dioxide released internally decreases, which is not conducive to the internal mineralization of the green body, so the mechanical properties, internal carbon fixation rate, and carbonization uniformity of the product are all reduced. When acetone dicarboxylic acid is not added to the admixture, guanidine bicarbonate cannot be generated in the admixture to cooperate with mixture A to improve the internal pore structure of the green body, and CO2 cannot be released internally to achieve internal mineralization, so the mechanical properties, internal carbon fixation rate and carbonization uniformity of the product are all deteriorated.

[0228] Comparison of Example 3 and Example 7 shows that in the process of preparing the admixture, diaminoguanidine hydrochloride, KH560 and acetone dicarboxylic acid are directly mixed and added without reacting in advance, and the mechanical properties and carbon fixation rate of the obtained carbon mineralized artificial stone are slightly reduced. It is speculated that the reason may be that the direct mixing method causes diaminoguanidine hydrochloride and KH560 to fail to generate mixture A in advance, which may make the binding force between the components in the system and the internal pore structure of the blank relatively worse, so the mechanical properties of the carbon mineralization product are slightly reduced.

Claims

1. A carbon mineralized artificial stone based on solid waste, characterized in that: The raw materials for preparation include: 39-125 parts of solid waste raw materials, 8-27 parts of aggregates, 0.1-0.5 parts of defoaming agent, 0.1-0.5 parts of water reducing agent, 0.1-1 parts of retarder and 2-15 parts of admixture; The raw materials for preparing the additive include aminoguanidine compounds, silane coupling agents and diacid compounds.

2. The solid waste-based carbon mineralized artificial stone according to claim 1, characterized in that: In parts by weight, the raw materials of the carbon mineralized artificial stone include: 51-112 parts of solid waste raw materials, 11-25 parts of aggregates, 0.1-0.3 parts of defoamers, 0.2-0.4 parts of water reducers, 0.3-0.7 parts of retarders and 4-11 parts of admixtures.

3. The solid waste-based carbon mineralized artificial stone according to claim 1, characterized in that: The solid waste raw materials include calcium solid waste, silicon-aluminum solid waste and gel solid waste; The defoaming agent is one or more of polyacrylamide, polyvinyl alcohol, silicone oil, and fatty alcohol; The water reducer is one or more of a polycarboxylate water reducer and a naphthalene water reducer; The retarder is one or more of a hydroxycarboxylate retarder, a polyalkyl carbohydrate retarder, and an inorganic compound retarder.

4. The solid waste-based carbon mineralized artificial stone according to claim 3, characterized in that: The mass ratio of the calcareous solid waste, the siliceous and aluminum-based solid waste and the gel solid waste is (25-65):(9-40):(5-20); The calcium solid waste is one or more of steel slag, magnesium slag, carbide slag, phosphorus slag, manganese slag, gypsum waste slag, purification ash, papermaking white mud, and chlor-alkali salt mud; The silicon-alumina solid waste is one or more of fly ash, glass tailings, coal gasification slag, furnace slag, bottom ash, red mud, steel slag, and coal gangue; The gel solid waste is one or more of industrial by-product waste cement, slag, limestone powder, desulfurized gypsum, iron tailings powder, metakaolin, and blast furnace slag.

5. The solid waste-based carbon mineralized artificial stone according to claim 1, characterized in that: The aminoguanidine compound is a combination of one or more of aminoguanidine bicarbonate, aminoguanidine hydrochloride, and diaminoguanidine hydrochloride; The diacid compound is a combination of one or more of acetone dicarboxylic acid and α-ketoglutaric acid; The silane coupling agent is a silane coupling agent having an epoxy group; Preferably, the silane coupling agent is a combination of one or more of KH560, hydrosil 2627 and hydrosil 2926.

6. The solid waste-based carbon mineralized artificial stone according to claim 1, characterized in that: The preparation method of the admixture is: (1) adding an aminoguanidine compound and a silane coupling agent to a solvent and stirring for 12-48 hours to obtain a mixture A; (2) fully mixing the mixture A and the diacid compound to obtain an admixture; The mass ratio of the aminoguanidine compound, the silane coupling agent and the diacid compound is 1:(1-8):(0.1-5); preferably, the mass ratio of the aminoguanidine compound, the silane coupling agent and the diacid compound is 1:(2-6):(0.4-4).

7. A process for preparing carbon mineralized artificial stone based on solid waste according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Pretreatment of solid waste raw materials: After the solid waste raw materials are powdered and screened, they are stored in a storage hopper for later use; S2. Mixing and stirring the ingredients: After the solid waste raw materials, aggregates, defoamers, water reducers, retarders and admixtures are fully mixed to obtain a mixture, water is added, and the mixture is fully mixed to obtain a wet material; S3, digestion, crushing and mixing: the wet material is transferred to the digestion system, digested, crushed, screened, and entered the next stage; S4, automatic fabric distribution: the automatic fabric distribution system realizes uniform and parameter-controllable fabric distribution; S5, compression molding process: the wet material is pressed into green billets in batches and enters the next stage; S6, pre-mineralization treatment: using low-concentration flue gas to pre-mineralize the green body; S7, CO2 graded mineralization treatment: using medium and high concentration CO2 gas to graded mineralize the pre-mineralized green body to obtain mineralized products; S8, polishing and grinding treatment: grinding and polishing the mineralized product to obtain a finished product; S9, fully automatic packaging, ready to go.

8. The process for preparing carbon mineralized artificial stone based on solid waste according to claim 7, characterized in that: The pre-mineralization temperature in step S6 is 10-90°C, and the mineralization time is 0.5-10h; the volume fraction of CO2 in the low-concentration flue gas is 2-55%; Preferably, the pre-mineralization temperature in the step S6 is 20-60° C., and the mineralization time is 1-8 hours; the volume fraction of CO 2 in the low-concentration flue gas is 3-45%.

9. The process for preparing carbon mineralized artificial stone based on solid waste according to claim 7, characterized in that: The graded mineralization in step S7 is as follows: Primary mineralization: mineralization pressure is 0.05-0.5MPa, mineralization temperature is 20-80℃, and mineralization time is 0.5-6h; secondary mineralization: mineralization pressure is 0.2-0.6MPa, mineralization temperature is 40-120℃, and mineralization time is 0.5-6h; tertiary mineralization: mineralization pressure is 0.4-1.0MPa, mineralization temperature is 60-120℃, and mineralization time is 0.5-6h; quaternary mineralization: mineralization pressure is 0.4-1.5MPa, mineralization temperature is 60-120℃, and mineralization time is 0.5-6h; the volume fraction of CO2 in the medium and high concentration CO2 gas is 8-99.99%.

10. The process for preparing carbon mineralized artificial stone based on solid waste according to claim 7, characterized in that: The graded mineralization in step S7 is as follows: Primary mineralization: mineralization pressure is 0.1-0.3MPa, mineralization temperature is 20-60℃, and mineralization time is 0.5-4h; secondary mineralization: mineralization pressure is 0.3-0.5MPa, mineralization temperature is 40-100℃, and mineralization time is 0.5-4h; tertiary mineralization: mineralization pressure is 0.5-0.7MPa, mineralization temperature is 80-100℃, and mineralization time is 1-4h; quaternary mineralization: mineralization pressure is 0.5-0.7MPa, mineralization temperature is 80-100℃, and mineralization time is 1-4h.

Citation Information

Patent Citations

  • Artificial rock material suitable for negative temperature environment and preparation method thereof

    CN113650132A

  • High-carbonization-degree and high-strength steel slag carbonized brick and preparation method thereof

    CN116514476A

Cited By

  • Vertical mineralization reactor, system and method for preparing artificial aggregate by mineralizing CO2

    CN121107729A

  • Vertical mineralization reactor, system and method for preparing artificial aggregates from CO2

    CN121107729B